Satisfaction of University Students with Teaching Performance, When Applying Virtual Teaching in the Context of COVID-19 - Chamorro-Atalaya, Omar Freddy (2022)
This article aims to analyze the satisfaction of university students from the per-spective of teaching performance, in face-to-face (2019-II) and virtual (2020-I) teaching-learning, due to the health emergency, declared in Peru, by COVID-19. These results will allow the Public University to implement continuous improve-ment plans in the teaching-learning development of the virtual environment. When performing the comparative analysis, it was determined that the careers that present the greatest satisfaction in 2020 - I, are business administration with 82.97% and systems engineering with 78.07%. Then it was identified that the in-dicators that present a greater negative variation are “The quality of the develop-ment of classes and activities“ with 5.88%, and “Treatment of students during class“, with 2.49%. With these results it can be indicated that the satisfaction of the students has presented a slight positive variation towards the teaching perfor-mance when applying the virtual modality.